2019
DOI: 10.1002/adom.201801453
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary Polarization Conversion with a Photonic Crystal Slab

Abstract: Our structure consists of a photonic crystal slab patterned with a square array of air holes introduced into the dielectric slab and a mirror underneath, as illustrated in Figure 1. We choose the periodicity of the structure such that within the wavelength It is shown that a simple photonic crystal slab structure provides a powerful mechanism for the control of the polarization properties of light. For a lossless system, for a given incident light with any fixed polarization, one can generate arbitrary polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…In recent years, great attention has been paid to modulate polarization of light with compact structures such as metasurfaces [4][5][6][7] instead of classical wave plates and polarizers, which are more applicable in on-chip devices. On the other hand, application of another kind of structure, photonic crystal (PhC) slab, in modulating polarization, is capturing interest nowadays [8][9][10][11]. Their simplicity in fabrication, designable band structures, and complex polarization features in the momentum space which are topologically linked with bound states in the continuum [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] are favorable for polarization modulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, great attention has been paid to modulate polarization of light with compact structures such as metasurfaces [4][5][6][7] instead of classical wave plates and polarizers, which are more applicable in on-chip devices. On the other hand, application of another kind of structure, photonic crystal (PhC) slab, in modulating polarization, is capturing interest nowadays [8][9][10][11]. Their simplicity in fabrication, designable band structures, and complex polarization features in the momentum space which are topologically linked with bound states in the continuum [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] are favorable for polarization modulation.…”
mentioning
confidence: 99%
“…On the other hand, application of another kind of structure, photonic crystal (PhC) slab, in modulating polarization, is capturing interest nowadays [8][9][10][11]. Their simplicity in fabrication, designable band structures, and complex polarization features in the momentum space which are topologically linked with bound states in the continuum [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] are favorable for polarization modulation. However, the reported PhC slabs only support nearly linearly polarized resonances which only cover a small area on the Poincaré sphere.…”
mentioning
confidence: 99%
“…The topological nature of EEs has spun-off several research efforts, exploring the merging of EE charges to produce even more confined resonances in realistic systems [26] and unidirectional guided modes within the continuum [27]. The topological properties of EEs have been especially useful for polarization control, as it was shown that topologically protected polarization conversion is possible [28][29][30], and circularly polarized states can arise from BICs by breaking spatial symmetries [31][32][33]. Recently, the generation of vortex beams through EEs [34] and efficient topological vortex laser generation [35] were demonstrated, showing the potential of topological phenomena in radiative and scattering processes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve high-density and multi-function on-chip integration, optical devices are required to expand their functions while further reducing their size. It is an alternative way to use elliptical polarization in order to increase information capacity [22,26]. However, existing elliptical polarization converters take advantage of transmission or reflection of metasurfaces, and convert light in free space, which are not easy to be compatible with on-chip integration [22].…”
Section: Introductionmentioning
confidence: 99%